The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/hep.22223
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparity in liver disease: Biological, cultural, or socioeconomic factors

Abstract: Chronic liver diseases are a major public health issue in the United States, and there are substantial racial disparities in liver cirrhosis-related mortality. Hepatitis C virus (HCV) is the most significant contributing factor in the development of chronic liver disease, complications such as hepatocellular carcinoma, and the need for liver transplantation. In the United States, African Americans have twice the prevalence of HCV seropositivity and develop hepatocellular carcinoma at more than twice the rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 62 publications
(67 reference statements)
5
137
0
1
Order By: Relevance
“…Previous studies have shown that the geographical distribution of HCV genotypes may have epidemiological relevance and clinical implications, such as response to therapy and disease progression (13). In addition, racial disparities might influence how HCV infection behaves, causing differences in the prevalence of HCV infection, clinical presentation, treatment response, and immunological recognition of HCV (18). It is deduced that these factors might have some impact on the characteristics of HCV anti-F antibody activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the geographical distribution of HCV genotypes may have epidemiological relevance and clinical implications, such as response to therapy and disease progression (13). In addition, racial disparities might influence how HCV infection behaves, causing differences in the prevalence of HCV infection, clinical presentation, treatment response, and immunological recognition of HCV (18). It is deduced that these factors might have some impact on the characteristics of HCV anti-F antibody activity.…”
Section: Discussionmentioning
confidence: 99%
“…Coronal and axial T 1 -weighted spin echo images of the whole liver were acquired for alignment and to determine liver volume (repetition time ϭ 500 ms; echo time ϭ 18 ms). 2 (95% air and 5% CO 2 ), and oxygen-CO 2 (95% oxygen and 5% CO 2 ) as described. 19,24 Five repeats were acquired at each gas mixture.…”
Section: Animalsmentioning
confidence: 99%
“…1,2 Evaluation of the level of liver pathological changes, such as cirrhosis, regeneration, or cancer, is important from both the diagnostic and the therapeutic aspects. Currently, there are limited tools for noninvasively monitoring these pathological alterations in the liver.…”
mentioning
confidence: 99%
“…However, it is not known whether SES influences the association between T2DM and CLDs, as it does for T2DM and cardiovascular disease [15]. The need for further research on the contribution of SES to disparities in incidence, treatment and outcomes of liver disease has previously been identified [16,17].…”
Section: Introductionmentioning
confidence: 99%